Bis(β-ketoiminate) dioxo tungsten(VI) complexes as precursors for growth of WOx by aerosol-assisted chemical vapor deposition. (1st September 2019) - Su, Xiaoming; Panariti, Persi; Abboud, Khalil A.; McElwee-White, Lisa
Graphical abstract: Bis(β-ketoiminate) dioxo tungsten(VI) complexes WO2 L2 (L = acNac, acNac Me, acNac Et ) have been synthesized and characterized. The performance of WO2 (acNac Me )2 as an AACVD precursor was evaluated at growth temperatures of 250–550 °C using nitrogen as the carrier gas. The deposited films were analyzed by XPS, XRD and SEM. Abstract: Bis(β-ketoiminate) dioxo tungsten(VI) complexes WO2 L2 (L = acNac, acNac Me, acNac Et ) have been synthesized and characterized. The thermal behaviors and possible decomposition mechanisms of these dioxo compounds were studied by TGA, MS and thermolysis. The performance of WO2 (acNac Me )2 as an AACVD precursor was evaluated at growth temperatures of 250–550 °C using nitrogen as the carrier gas. The elemental compositions of the as-deposited and sputtered tungsten oxide films were determined by XPS. The morphology and stoichiometry of the as-deposited films were studied by SEM and XRD.